Analisis Modifikasi Alur Kampas Ganda dan Clutch Housing CVT terhadap Torsi Mesin 110cc (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of automotive technology drives innovation in vehicle support components, including the continuously variable transmission (CVT) system, which plays a crucial role in transmitting engine torque and power to the wheels. One of the main elements in this system is the clutch lining and clutch housing, whose performance significantly impacts motorcycle performance. However, the standard pattern on these components is often not optimal in maximizing power delivery. Therefore, this study was conducted to analyze the effect of modifying the grooves of the clutch lining and clutch housing on engine torque in a 110 cc motorcycle. The research method used an experimental approach by varying the modification pattern on the clutch lining and clutch housing. The test motorcycle with a capacity of 110 cc was tested using a dyno test to measure torque and power at various engine speeds. Each modification variation was then compared with standard conditions to evaluate the resulting performance differences. The results showed that the pattern modifications on the clutch lining and clutch housing significantly increased torque. Several modification variations were able to significantly increase torque at medium to high speeds, thus providing better engine response and more efficient power delivery. Thus, this research contributes to the development of more optimal CVT component designs and has the potential to improve motorcycle performance, especially in the small capacity vehicle segment.